Landfalling tropical cyclones on the Pacific coast of Mexico: 1850-2010 - Graciela B. Raga; BEATRIZ BRACAMONTES CEBALLOS; LUIS MANUEL FARFAN MOLINA; Rosario Romero-Centeno (Universidad Nacional Autónoma de México. Centro de Ciencias de la Atmósfera, 2013)
Historical documents and newspapers from Mexican Pacific states (north of 14º N) were reviewed to determine the incidence of landfalling tropical cyclones from 1850 to 1949, prior to the start of the United States National Hurricane Center database. The reviewed documents are only found in Mexican repositories at national, state and municipal level and the systematic search embarked upon in this study yielded valuable information that cannot be found elsewhere. A time series of landfall was reconstructed back to 1850, indicating active and quiet periods. An average of 1.8 ± 1.6 landfalls per year is determined from the time series for 1850-2010. When the series is limited to 1880-2010, eliminating the first 30 years that may have some undercounting, the average increases to 2.1 ± 1.6 cases per year. Spectral and wavelet analysis of the 161 years of landfalling tropical cyclones indicates that the Pacific Decadal Oscillation (PDO) modulates the activity. The influence of El Niño/Southern Oscillation(ENSO) and the North Atlantic Oscillation (NAO) on the landfall frequency may be present throughout the reconstruction period but both oscillations have lower correlations compared to that from the PDO.